Lea Goldberg in the Age of Extremes: Poetics of Recovery in Times of WarLea War - Abadi, Shai (MiKAN, 2024)
Lea Goldberg was born in 1911 to a Jewish Lithuanian family from Kaunas. After the outbreak of World War I, the Goldberg family left Kaunas to seek refuge in Russia. During these years, and in the years following the war, eight-year-old Lea went through some formative events that profoundly affected her life and work. The article suggests that on the eve of World War II, the young poet experienced a personal crisis stemming from the reoccurrence of traumatic events she endured during World War I. By examining Goldberg’s essayistic writing during the 1930s, alongside her belletristic writing, the article contends that the poet bore witness and retold for the first time the traumatic events she experienced 20 years earlier. However, at the onset of World War II, Goldberg had a radical change of heart, publicly denouncing wartime literature and opposing the option of poetic witness-bearing in times of war. As the proposed reading of the poet’s wartime poetry suggests, her work in those years might be termed “therapeutic poetry” – a poetry which became useful for contemporary readers in an age of extremes. By examining the war poetics of Lea Goldberg, the article offers a new understanding of the highly complex reciprocal relationship between literature, history and psychology.